Population Migration to Juba City since the Comprehension Peace Agreement: Impacts and Consequences - Okic Yor, Angelo (IJRDO Journal of History & Geography, 2021)
The paper tried to analyze the causes of population migration to Juba City since the Comprehensive Peace Agreement: Impacts and Consequences. The aims of this paper are to discover the background of the migrants with regard to their areas of origin; why they migrated, the causes, the impacts and consequences of their migration to Juba City, to discuss their patterns of settlement in Juba City as well as the issues of adjustment and livelihood support and propose the solutions to the problems facing migrants in Juba City. This study used a personal interview and questionnaire method for the purposes of data collection from three payams selected in Juba City. Also, the study used secondary data sources such as references, public records, organizational records, census data, previous studies and surveys. In analysis of data sets, descriptive statistical method was employed for the purpose of getting the background characteristics of the migrants’ households in Juba City using frequencies, and percentages distribution Tables. However, the findings of the study indicate that almost half of migrants (56%) were generated by war/conflict, also floods, famine/drought displaced many people. In addition, the study found that view migrants are facing problems of job opportunities and inadequate housing in Juba City. The Capital Cities are favorable places for facilities and investments and these accounts for their special attractions to migration, especially from rural to urban migration. In conclusion, South Sudan mass population migration to Juba City (2005-2015) was due to economic factors such as seeking for job opportunities, social factors such as education and health services beside war and conflict, drought, floods, famine, epidemics, food security and stability and development trend in the country. The study defined the concept of migration and identified the types of migration and the theories; difficulties that face the migrants in Juba City and the problems faced by the migrants in the towns, beside the impacts and the consequences of migration on both source and receiving areas. The study recommended that migrants should be empowered through capacity building programs to ensure that they adopt self-reliant attitudes, integration them with the host communities to reduce the socio- cultural and psychological gaps that exist between them. The root causes of migration must be properly identified recognized, and solutions sought to address them, their opinions should be taken into consideration whether they remain in Juba or return to their respective home towns or areas of origin, government should create job opportunities and establish schools, health care centers and social amenities such as water supply for migrants as well as for the general population. Moreover, the NGOs and governmental organizations should cooperate and contribute toward promotion of human rights and respect migrants from rights violation, the international community and the World Bank should provide helpful hand to South Sudan to make successful projects for resettlement of migrants. Also, populace of South Sudanese should search and contribute to achieve permanent peace in the country.